Covert Warriors - Butterworth, William E. (William Edmund) (New York : Jove Books, 2013)
When a hostile Third World country begins to receive military training and nuclear technology from foreign nations, Charley Castillo and his team investigate only to be abandoned by the U.S. government and placed on hit lists throughout the world.
Keywords: United States -- Army; Delta Force -- Fiction; Castillo, Charley (Fictitious character) -- Fiction; Undercover operations -- Fiction; International relations -- Fiction; Spy stories; Thrillers (Fiction)